2011
DOI: 10.1007/s12105-011-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor with Entrapment of Minor Salivary Gland Tissue: An Unusual Presentation That Requires Exclusion of Pleomorphic Adenoma

Abstract: We report two unusual cases of solitary fibrous tumor (SFT) of minor salivary glands that microscopically mimicked pleomorphic adenoma. One of these lesions presented in the retromolar region and the other in the buccal mucosa. The microscopic features of these two tumors and their intimate relationship with regional mucous minor salivary glands posed a diagnostic challenge. Awareness of the morphological diversity of SFT coupled to a judicious use of appropriate immunohistochemical probes should prove valuabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…SFT and hemangiopericytoma display immunoreactivity for CD34, Bcl-2 and CD99 antigens. Ultrastructural studies have demonstrated pericytic, fibroblastic, and myofibroblastic differentiation in both tumors [3,16]. These findings have led pathologists to consider hemangiopericytoma and SFT as a spectrum of the same entity [22].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…SFT and hemangiopericytoma display immunoreactivity for CD34, Bcl-2 and CD99 antigens. Ultrastructural studies have demonstrated pericytic, fibroblastic, and myofibroblastic differentiation in both tumors [3,16]. These findings have led pathologists to consider hemangiopericytoma and SFT as a spectrum of the same entity [22].…”
Section: Discussionmentioning
confidence: 98%
“…Anti-CD34 antibody, which recognizes a 110-kDa transmembrane cell surface glycoprotein found on myeloid progenitor cells, is the most consistent and reliable immunohistochemical marker for SFT [14][15][16]. On the other hand, neoplastic cells are negative for cytokeratins, S-100 protein, epithelial membrane antigen, smooth muscle actin, and Factor VIII [13,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 70 cases have been described in the English-language literature. 26 The buccal mucosa is the most common site of occurrence, followed by the tongue, gingiva, palate, lip, buccal sulcus, posterior trigone, and mental region (Table 2). 17,22,27 In the Italian literature, only 2 cases of SFT of the infratemporal fossa, 4 1 case in the laterocervical spaces, 28 and 1 case in the parapharyngeal space 8 have been described.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27]29,30 Diagnosis of SFT can only be performed by histologic examination, because clinical signs and radiologic features are not specific enough. The tumor microscopic aspect shows spindle or ovoid cells associated with collagenous matrix and branched vessels with a hyaline wall.…”
Section: Discussionmentioning
confidence: 99%